Phenolic composition, antioxidant and enzyme inhibitory activities of Cucurbitaceae fruits - Ramirez, Maria Rosana (2018)
Fruits have been known as great source of bioactive natural compounds with potential biological effects. The objective of this work was to perform digestive enzyme inhibition assays with methanolic extracts of six fruits from the family Cucurbitaceas. The extracts were also analyzed for antioxidant capacity (DPPH·), qualitative and quantitative composition of chemical compounds and nutrients. The fruit extracts showed similar antioxidant activities and had substantially different total polyphenolic contents. In addition, the six fruit extracts examined, at a concentration of 100 μg/mL, significantly inhibited β glucosidase and lipase activity, in vitro. These results may be related to the profile of polyphenolic compounds. In conclusion, it can be said that cucurbits fruits are a valuable horticultural product, based on their rich and beneficial chemical composition.